Optimalisiasi Kesadaran Hukum Masyarakat mengenai Penyelesaian Pembiayaan Bermasalah Tanpa Agunan melalui Gugatan Sederhana yang Dikemas dalam Pelatihan Berperspektif Hukum Perikatan dan Perjanjian - Yuyut Prayuti; Yeni Nureaeni; L. Alfies Sihombing; Mia Rasmiaty; Elis Herlina (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
In the evolving dynamics of Indonesia's economy, unsecured loans or Kredit Tanpa Agunan (KTA) have rapidly grown as a popular financial solution. The ease of application and fund disbursement makes these products especially attractive to micro-entrepreneurs and lower-middle-income communities. However, behind the convenience lies a serious issue: a high rate of default or breach of contract (wanprestasi). This problem is exacerbated by the low level of legal literacy among the public, leading to a lack of understanding of their rights and obligations in financing agreements. Most individuals are also unaware that there is a faster, simpler, and low-cost legal mechanism available for resolving civil disputes—namely, the Small Claims Court procedure, as regulated by the Supreme Court Regulation (Perma) No. 4 of 2019. This mechanism can be utilized by the general public, especially clients of microfinance institutions and credit cooperatives, to resolve civil conflicts involving claims of up to IDR 500 million without going through complex litigation. To address this issue, this community engagement activity aimed to improve public legal understanding of the Small Claims Procedure through participatory-based training. The training involved 50 participants from microfinance institutions and savings and loan cooperatives. The methods used included legal counseling, mock court simulations, group discussions, and case studies to provide participants with practical knowledge of the procedures and benefits of filing small claims. The results of the activity indicated that 78% of participants reported a better understanding of the Small Claims mechanism after the training, and 65% stated they were more inclined to use it compared to conventional litigation routes. This training had a positive impact on raising legal awareness, potentially reducing default rates, and contributing to the development of a more inclusive, fair, and sustainable financial system.